The KPU, Bawaslu, and the Constitutional Court in Resolving Disputes in Indonesia's Regional Elections: Negotiating and Navigating Authority and Cooperation - titis anindya (Asia-Pacific Journal of Elections and Democracy, 2022)
There were a few issues with how the General Election Commission (Komisi Pemilihan Umum, or KPU) followed up with the Election Supervisory Agency (Badan Pengawas Pemilu, or Bawaslu) in carrying out the dispute resolution for the 2020-2021 regional elections (Pemilihan Umum Kepala Daerah, or Pilkada). These issues were raised by the petitioners in their lawsuit before the Constitutional Court (Mahkamah Konstitusi, or MK). The petition suggests that there is a critical issue in the distribution of authority between Bawaslu and KPU. Similarly, the Court cannot resist adopting the KPU and Bawaslu's control over difficulties that continuously grow during elections. Reflecting on this situation, this study analyzes and investigates the KPU's and Bawaslu's positions of authority as the organizers of the regional election, as well as the Court's position regarding the follow-up to Bawaslu's recommendations. This is a normative legal study based on literature. The KPU and Bawaslu have equal jurisdiction in resolving administrative violations of the Regional Election. KPU decisions are founded on Bawaslu recommendations, and vice versa; Bawaslu suggestions constitute a type of control over the KPU before it goes through the decision-making process. The Court will decide whether or not to implement Bawaslu's suggestions on a case-by-case basis, based on the concept of benefit and prioritizing legitimacy and purity of voice, rather than rigidly applying the regulations.